In the face of gentrification : a case study of social capital in supporting community efforts to form a collective action - Azka Nur Medha; Putu Gde Ariastita (IPTEK The Journal of Engineering, 2017)
Gentrification is believed to be an urban phenomenon that has a negative impact on neighborhood society. Therefore, the neighborhood community becomes an important study object in order to understand the process of gentrification itself. This study observes the community in Medokan Semampir community group, Surabaya, that raised a case study in which they made collective action to face gentrification. Collective action can be viewed as a solution in order to facilitate the common interests of a gentrified community. The aim of this paper is to explain the collective action process in the context of social capital, and how communities can keep the capital as collective assets to prevent gentrification processes anguish its members.